AI Projects for Computer Science Capstone Classes (Extended Abstract) - Taylor, Matthew; Arslan Ay, Sakire (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Capstone senior design projects provide students with a collaborative software design and development experience to reinforce learned material while allowing students latitude in developing real-world applications. Our two-semester capstone classes are required for all computer science majors. Students must have completed a software engineering course — capstone classes are typically taken during their last two semesters. Project proposals come from a variety of sources, including industry, WSU faculty (from our own and other departments), local agencies, and entrepreneurs. We have recently targeted projects in AI — although students typically have little background, they find the ideas and methods compelling. This paper outlines our instructional approach and reports our experiences with three projects.